India’s Agricultural Marketing Market Reforms and Emergence of New Channels - Ghosh, Nilabja. (India Studies in Business and Economics,, 2013)
The proposed book provides an assessment of an important yet controversial policy initiated by the Indian government and governments of several other developing countries. Marketing reforms, it is claimed, can be a crucial answer to solving the problem of rural poverty in agrarian economies where large sections of populace are engaged in low paying agriculture. On a wider front, these reforms could help in providing growth impetus to an economy and even the global economy at large.  Yet, the subject of liberalizing agricultural markets is also part of a broad and perhaps a bitter political debate between national and sub-national policy makers and academic discourses in India and other countries. A clearer understanding and a possible resolution of the issues involved will be decidedly useful. The experience of India, one of the largest and most agriculture-dominated economies, will undoubtedly provide valuable lessons not only for steering the domestic economic policy but also for other countries to set their own policy agenda. The book attempts to capture the evolving reality in a large and diverse country and presents an objective evaluation to enable aspiring investors and those in policy making, food business and civil society to make more informed assessment and decision.